Developing new approaches to ethics research integrity training through challenges posed by creative practice research : final report. - Bolt, Barbara; MacNeill, Kate; McPherson, Megan; Ednie-Brown, Pia; Wilson, Carole; Miller, Sarah; Barrett, Estelle; Sierra, Marie (Australia. Dept of Education and Training (DET), 2018)
The project arose out of a realisation that with creative practice research, a relatively new field of research in the university context, the current cohort of research higher degree (RHD) candidates were negotiating ethics procedures that their supervisors may not have needed to comply with in their academic careers. The project aimed to develop a robust, innovative and ethically informed research ethics culture in the creative arts and design discipline, by equipping graduates with the ethical know-how for their real-world professions as artists and designers. The project was designed to determine what resources might benefit RHD candidates, their supervisors and ethics administrators. A combination of quantitative and qualitative, creative art and design methods informed the outcomes. Data collection took place predominantly across Australian universities and attracted 116 respondents across all fields of creative practice: art, design, object and interior design, sound, video, interactive media, architecture, music and music composition, journalism, creative writing, dance, and theatre and performance, and the multidiscipline approaches of creative arts practice. In addition to an online survey the project team conducted interviews with 29 respondents. In addition to these conventional methods of data collection, the project team facilitated workshops at a range of locations, which were designed as experiential and active learning events, and the discussions therein also contributed to the information and resources utilised to design the ethics toolkit. The toolkit also contains a handbook, resources and outlines of pedagogical workshops that can be conducted with RHD candidates. [Executive summary, ed]